ANALISIS KONTRIBUSI SEKTOR PARIWISATA TERHADAP PENINGKATAN KESEJAHTERAAN EKONOMI MASYARAKAT DESA BENOA KABUPATEN BADUNG - Fahmi Tanjung; Yoviniani Yevri Yanseni; I Made Sujana; Putu Ratna Windusara Putri (Nusantara Hasana Journal, 2024)
Tourism is a strategic sector that contributes significantly to the economic growth of Badung Regency, particularly in the Benoa Village area, which is developing as a marine tourism destination and supporting the Nusa Dua tourism area. This study aims to analyze the contribution of the tourism sector to improving the economic welfare of the Benoa Village community. The tourism sector has a positive influence on regional economic growth through increased community income, employment opportunities, and productive business activities. Tourism development can improve the economic conditions of local communities through job creation and the expansion of informal sector businesses. The results of the study indicate that the tourism sector contributes significantly to increasing household income, employment opportunities, and the economic welfare of the Benoa Village community.